CD163 protein inhibits lipopolysaccharide-induced macrophage transformation from M2 to M1 involved in disruption of the TWEAK–Fn14 interaction - Linjian Chen; Wanchun Mei; Juan Song; Kuncheng Chen; Wei Ni; Lin Wang; Zhaokai Li; Xiaofeng Ge; Liuhang Su; Chenlu Jiang; Binbin Liu; Cuilian Dai (Heliyon, 2024)
Macrophages play a crucial role in regulating inflammation and innate immune responses, and their polarization into distinct phenotypes, such as M1 and M2, is involved in various diseases. However, the specific role of CD163, a scavenger receptor expressed by macrophages, in the transformation of M2 to M1 macrophages remains unclear. Here, dexamethasone-induced M2 macrophages were treated with lipopolysaccharide (LPS) to induce the transformation of M2 to M1 macrophages. We found that treatment with lipopolysaccharide (LPS) induced the transformation of M2-like macrophages to an M1-like phenotype, as evidenced by increased mRNA levels of Il1b and Tnf, decreased mRNA levels of Cd206 and Il10, and increased TNF-α secretion. Knockdown of CD163 enhanced the phenotypic features of M1 macrophages, while treatment with recombinant CD163 protein (rmCD163) inhibited the LPS-induced M2-to-M1 transformation. Furthermore, LPS stimulation resulted in the activation of P38, ERK, JNK, and NF-κB P65 signaling pathways, and this activation was increased after CD163 knockdown and suppressed after rmCD163 treatment during macrophage transformation. Additionally, we observed that LPS treatment reduced the expression of CD163 in dexamethasone-induced M2 macrophages, leading to a decrease in the CD163-TWEAK complex and an increase in the interaction between TWEAK and Fn14. Overall, our findings suggest that rmCD163 can inhibit the LPS-induced transformation of M2 macrophages to M1 by disrupting the TWEAK-Fn14 interaction and modulating the MAPK–NF–κB pathway.